스마트폰 구매결정요인이 브랜드신뢰와 구매의도에 미치는 영향 - 유익상(Yoo, Ik Sang) (한국디자인리서치, 2022)
연구의 목적은 오늘날 스마트폰 사용자들의 트렌드가 반영된 구매 결정 요인들의 선행연구들을 근거로 정의한 네 가지 주요 요인들이 브랜드신뢰에 미치는 요인과 브랜드 신뢰, 구매의도에 미치는 영향을 각각 살펴보는 것에 있다. 연구대상의 범위는 세계 스마트폰 시장을 양분하고 있는 애플과 삼성 제품으로 한정하였다. 연구방법은 설문조사법을 활용하여, 2021년 10월 4일부터 22일까지 총 150부의 설문지를 배포, 실시하였으며, 중복표기, 누락 등 잘못 기재된 설문지 9부를 제외하고 총 141부를 수거하여 가설 검증에 앞서 각 변수의 신뢰성 및 타당성 측정을 위한 요인분석과 회귀분석을 실시하였다. 가설검증을 위해 통계패키지로는 SPSS 25.0와 AMOS 25.0 을 사용하였다. 피험자들을 대상으로 실시한 빈도분석 결과, 스마트 폰 평균 사용주기는 2~3년으로 56%(79명)이었으며, 활용빈도에서는 동영상시청이 63.1%(89명)로 가장 높게 나타났다. 구매결정요인들이 브랜드신뢰에 미치는 영향을 살펴보기 위해 설정한 대립가설을 검증하고, 인과관계 분석을 위한 다중회귀분석을 실시한 결과 두 브랜드 모두 네 가지 요인들 중 브랜드 요인만이 통계적으로 유의미하게 나타났다. 마지막으로 브랜드요인이 영향을 미친 브랜드신뢰도가 구매의도에 미치는 영향에 대한 단순회귀분석 결과, 영향 정도를 나타내는 ß값에서 삼성제품이 0.349, 애플제품이 0.205로 도출되어 삼성제품이 다소 보다 높게 나타났으나, 통계적으로 큰 의미를 찾을 수 없었다. 브랜드신뢰도가 구매의도에 미치는 영향에 대한 가설은 전체적으로 귀무가설이 기각되는 결과로 나타나 통계적으로 유의미한 결과가 도출되었다. The purpose of this study is to define the purchasing decision factors reflecting the trend of today's smartphone users into four main factors based on previous studies, analyze the factors affecting brand trust, and examine the influence of brand trust on purchase intention. it is in The scope of the research subject was limited to the products of Apple and Samsung, which are bisecting the global smartphone market. A total of 141 copies were collected except for 9 questionnaires that were incorrectly filled out with duplicates and omissions, and factor analysis and regression analysis were performed to measure the reliability and validity of each variable prior to hypothesis testing. For hypothesis testing, statistical packages SPSS 25.0 and AMOS 25.0 were used. As a result of the frequency analysis conducted on the subjects, the average smartphone use cycle was 2 to 3 years, 56% (79 people), and in terms of the frequency of use, watching a video was the highest at 63.1% (89 people). As a result of testing the alternative hypothesis established to examine the influence of purchasing determinants on brand trust and performing multiple regression analysis for causality analysis, only the brand factor among the four factors for both brands was found to be statistically significant. Finally, as a result of a simple regression analysis of the effect of brand reliability influenced by brand factors on purchase intention, the ß value indicating the degree of influence was derived for Samsung products as 0.349 and for Apple products as 0.205, indicating that Samsung products are somewhat higher. However, no statistical significance was found. As for the hypothesis on the effect of brand reliability on purchase intention, the null hypothesis was rejected as a result, resulting in statistically significant results. KCI Citation Count: 0